2024
DOI: 10.1126/science.adk9099
|View full text |Cite
|
Sign up to set email alerts
|

A deep reservoir for hydrogen drives intense degassing in the Bulqizë ophiolite

Laurent Truche,
Frédéric-Victor Donzé,
Edmond Goskolli
et al.

Abstract: Deep crustal production of hydrogen (H 2 ) is a potential source of primary energy if recoverable accumulations in geological formations are sufficiently large. We report direct measurements of an elevated outgassing rate of 84% (by volume) of H 2 from the deep underground Bulqizë chromite mine in Albania. A minimum of 200 tons of H 2 is vented annually from the mine’s galleries, making it one of the largest recorded H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Notably, this study found no correlation between hydrogen and helium concentrations but did observe substantial organic and crustal contributions (CH 4 and N 2 ). Contrastingly, recent data from South Australia and direct measurements from the Bulqizë chromite mine in Albania report significant hydrogen outgassing, with H 2 concentrations >80% and varying but minor N 2 , CO 2 and CH 4 components (Goh, 2023;Gold Hydrogen, 2023;Truche et al, 2024;Yeo, 2023). Interestingly, whilst the results of Lévy et al (2023a) indicated no a clear connection between hydrogen and helium in the context of serpentinization, Karolytė et al (2022) documented He-rich hydrocarbon gases in South Africa's Witwatersrand Basin, where the scarcity of mafic and ultramafic minerals capable of serpentinization suggests radiolytic hydrogen production as the predominant mechanism.…”
Section: Recent Hydrogen Discoveries and Possible Importance To Migra...mentioning
confidence: 75%
See 2 more Smart Citations
“…Notably, this study found no correlation between hydrogen and helium concentrations but did observe substantial organic and crustal contributions (CH 4 and N 2 ). Contrastingly, recent data from South Australia and direct measurements from the Bulqizë chromite mine in Albania report significant hydrogen outgassing, with H 2 concentrations >80% and varying but minor N 2 , CO 2 and CH 4 components (Goh, 2023;Gold Hydrogen, 2023;Truche et al, 2024;Yeo, 2023). Interestingly, whilst the results of Lévy et al (2023a) indicated no a clear connection between hydrogen and helium in the context of serpentinization, Karolytė et al (2022) documented He-rich hydrocarbon gases in South Africa's Witwatersrand Basin, where the scarcity of mafic and ultramafic minerals capable of serpentinization suggests radiolytic hydrogen production as the predominant mechanism.…”
Section: Recent Hydrogen Discoveries and Possible Importance To Migra...mentioning
confidence: 75%
“…The relationship between fluid migration and helium is paradoxical, given that for high He concentrations to be preserved alongside high H 2 concentrations (e.g., Gold Hydrogen, 2023), migration must be rapid enough to prevent dilution whilst the isolation of fluids over billions of years could allow He to accumulate whilst H 2 is lost (e.g., Karolytė et al, 2022). The relationship between surface gas seep compositions and migration pathways is more nuanced, given that microbial methanogenesis (Table 5) is depth-dependent (e.g., Truche et al, 2024). Hydrogen consumption within the shallowest levels of the subsurface (<1 m) may imprint a diurnal variation onto otherwise long-lived high-concentration (>50%) H 2 signals (e.g., Myagkiy, Moretti, & Brunet, 2020).…”
Section: Recent Hydrogen Discoveries and Possible Importance To Migra...mentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the global shift toward sustainable energy sources, naturally occurring H 2 has garnered significant attention as a putative carbon-neutral energy alternative to traditional fossil fuels. This interest is reflected in recent research exploring the potential of H 2 in various geological contexts (Donzé et al, 2020;Moretti et al, 2021;Prinzhofer et al, 2018; N. J. P. Smith et al, 2005;Truche et al, 2024). Current exploration methodologies for targeting H 2 in potential geological reservoirs predominantly rely on soil gas analysis at a depth of approximately 1 m. However, this approach is somewhat limited in scope and does not encompass a comprehensive and efficient methodology.…”
Section: Introductionmentioning
confidence: 99%
“…It can be produced from renewable or non-renewable energy sources [1]. Despite the newest reports indicating possible accumulations of hydrogen in geological formations [2,3], by 2023, 84% of the hydrogen produced came from fossil sources, including 62% from natural gas, according to data from the International Energy Agency (IEA) [4]. The steam reforming of methane is recognized as the predominant technique for hydrogen production.…”
Section: Introductionmentioning
confidence: 99%